Robust Joint Optimization for Efficient and Reliable FSO/RF Satellite-UAV-Terrestrial Networks With Random Fading and Imperfect Channel Information - Li, Xiaoyan; Liu, Yitong; Guo, Shaoai; Li, Zan; Zhao, Xiaohui (IEEE internet of things journal, 2025)
This study focuses on a free space optical (FSO)/radio frequency (RF) satellite-UAV-terrestrial integrated network (SUTIN) to overcome limitations of traditional RF SUTIN on spectrum scarcity and security. Traditional resource allocations for FSO/RF SUTIN often prioritize transmission efficiency while neglecting reliability. Moreover, in this network, atmospheric turbulence, pointing errors, and multipath fading can lead to unreliable data transmission. To resolve these problems, we propose a hybrid FSO/RF SUTIN based on adaptive modulation and coding schemes (MCS) and resource allocation algorithm to ensure both transmission efficiency and reliability with imperfect channel state information (CSI) and random channel fading. A joint optimization problem is formulated, incorporating MCS mode selection, power allocation, and UAV trajectory optimization, with frame error rate (FER) and CSI uncertainty constraints to maximize system throughput. To solve this complicated high dimension optimization problem, we present mathematical mapping models between the optimization variables and communication performance parameters (the average transmission rate and FER) with imperfect CSI and random fading for both FSO and RF link. According to these mapping models, a robust solution based on deep deterministic policy gradient is proposed, integrating decoupling and user clustering techniques to reduce the computational complexity. The simulation results demonstrate that this proposed FSO/RF SUTIN and the corresponding algorithm can improve system throughput and guarantee transmission reliability.